PENYULUHAN TENTANG KHASIAT TANAMAN KECOMBRANG DI MASYARAKAT UNTUK PENYEMBUHAN LUKA BAKAR DI DESA BIRU-BIRU - Zola Efa Harnis; Ayu Meta Sari Br. Perangin-angin (INSTITUT KESEHATAN DELI HUSADA, 2021)
Kecombrang plant is one of the medicinal plants that can be used as traditional medicine. This plant is commonly known as bongkot. Kecombrang plants are generally used by the community as a flavor enhancer of cuisine and used as traditional medicine, which the community believes is able to eliminate body odor, bad breath, improve blood circulation and heal wounds and can increase breast milk for nursing mothers. This counseling aims to obtain data on providing counseling about the efficacy of the kecombrang plant in the community for healing burns in the Biru-biru village. Counseling was carried out with an interactive method between the presenters and participants so that the event took place in an interesting manner and provided education to the community about the benefits of the kecombrang plant as a burn treatment in Biru-biru Village. The results obtained from this counseling are a lack of understanding or lack of knowledge of the community following counseling in Biru-biru Village about the use of the kecombrang plant as a burn treatment, by providing guidance and assistance with counseling methods, the results obtained where the community, especially those who participated in the counseling, showed enthusiasm in curiosity. from the benefits of the kecombrang plant as a burn treatment as well as the increased experience and knowledge of the people of Biru-biru Village who participated together in counseling the benefits of the kecombrang plant as a burn treatment through materials and simulations obtained during socialization. The conclusion of this counseling is that the community has been able to find out the benefits of the kecombrang plant as a burn treatment.